2018
DOI: 10.1155/2018/9704892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Anterior Lens Epithelial Cell Removal on Axial Position of Intraocular Lens after Cataract Surgery

Abstract: Purpose The aim of this study was to assess the effects of residual anterior lens epithelial cell (LEC) removal by anterior capsule polishing on the effective lens position (ELP) and axial position stability of the intraocular lens (IOL) after cataract surgery via postoperative measurement of the anterior chamber depth. Methods We enrolled 30 patients (60 eyes) requiring bilateral cataract surgery for age-related cataracts. Meticulous anterior capsule polishing and removal of residual LECs under the capsule we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A previous study indicated decreasing the polishing of anterior capsule enhances the rotational rmness of a toric IOL [18] . However, a study involving 30 patients (60 eyes) revealed that the eyes that did not undergo intraoperative ACP had a likelihood for backward IOL movement by about 0.2mm, at two months after surgery [19] . Another study posited that 360° ACP effectively reduces the incidence of the anterior capsule contraction and raises the rmness of IOL in cataract patients with high myopia [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated decreasing the polishing of anterior capsule enhances the rotational rmness of a toric IOL [18] . However, a study involving 30 patients (60 eyes) revealed that the eyes that did not undergo intraoperative ACP had a likelihood for backward IOL movement by about 0.2mm, at two months after surgery [19] . Another study posited that 360° ACP effectively reduces the incidence of the anterior capsule contraction and raises the rmness of IOL in cataract patients with high myopia [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intraoperative ACP might not be a routine choice for ophthalmologists to reduce the incidence of PCO. However, the role of ACP in maintaining the stability of IOL cannot be ignored, especially for MIOL, because some studies have shown that it reduces the occurrence of ACO and the anterior capsule contraction [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…ECD levels below 800/mm 2 can result in corneal edema. Several risk factors are known to accelerate this loss, including intraocular surgery, trauma and glaucoma [5][6][7][8][9][10][11][12].…”
Section: Changes In the Density Of Corneal Endothelial Cells In Elderly Diabetic Patients After Combined Phacovitrectomy And Ex-press Glamentioning
confidence: 99%
“…Surgery should be performed during this period in patients with lens opacity, which leads to an unclear visual axis [ 4 ]. Continuous circular capsulorhexis (CCC) is the key and challenging step in cataract surgery, which influences the intraocular lens (IOL) position and postoperative refraction [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%